2023
DOI: 10.1038/s41419-023-05891-0
|View full text |Cite
|
Sign up to set email alerts
|

FBXO7, a tumor suppressor in endometrial carcinoma, suppresses INF2-associated mitochondrial division

Abstract: Endometrial carcinoma (ECa) is the most common malignant gynecological cancer, with an increased incidence and fatality rate worldwide, while the pathogenesis is still largely unknown. In this study, we confirmed that FBXO7, a gene coding FBXO7 E3 ubiquitin ligase, is significantly downregulated and mutated (5.87%; 31/528) in ECa specimens, and the abnormal low expression and mutations of FBXO7 are associated with the occurrence of ECa. We also identify the excessive expression of INF2 protein, a key factor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…On the other hand, the atypical ubiquitination of INF2 by the CRL3 SPOP ubiquitin ligase complex reduces its ER localization and inhibits mitochondrial division [ 32 ]. Moreover, a recent study has identified that F-box protein 7 (FBXO7) induces ubiquitination and degradation of INF2, thereby inhibiting INF2-DRP1 axis-associated mitochondrial fission [ 15 ]. Our findings contribute to the understanding of INF2 post-translational modifications, demonstrating that increased phosphorylation of INF2 Ser1077 in EC cells enhances ER localization, leading to greater recruitment of DRP1 to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the atypical ubiquitination of INF2 by the CRL3 SPOP ubiquitin ligase complex reduces its ER localization and inhibits mitochondrial division [ 32 ]. Moreover, a recent study has identified that F-box protein 7 (FBXO7) induces ubiquitination and degradation of INF2, thereby inhibiting INF2-DRP1 axis-associated mitochondrial fission [ 15 ]. Our findings contribute to the understanding of INF2 post-translational modifications, demonstrating that increased phosphorylation of INF2 Ser1077 in EC cells enhances ER localization, leading to greater recruitment of DRP1 to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Mdivi-1, which was first identified in 2008, inhibits DRP1 assembly and GTPase activity, thereby inhibiting mitochondrial fission [ 37 ]. Mdivi-1 has demonstrated the ability to inhibit the proliferation and migration of EC cells, possibly by regulating reactive oxygen species in mitochondria [ 15 ]. Given that high INF2 expression enhances EC proliferation by promoting mitochondrial division, inhibition of mitochondrial division may be a viable approach for the treatment of EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…INF2 protein in the ER can trigger mitochondrial division by recruiting DRP1 protein, and elevated INF2 has been significantly, negatively correlated with the hypocancerous FBXO7 protein in endometrial cancer specimens ( 98 ). Under energetic stress conditions, AMPK induces phosphorylation of INF2 (Ser1077), leading to its increased localization to the ER, which enhances DRP recruitment to mitochondria and promotes endometrial cancer cell growth ( 99 ).…”
Section: Cellular Organelle Mechanisms In Endometrial Cancer Pathogen...mentioning
confidence: 99%
“…In terms of its SCF-dependent function, FBXO7 interacts with and ubiquitinates specific substrates, thus regulating several cellular processes, including mitophagy 21 , proteasomal assembly 22 , and glycolysis 23 . Recent studies have demonstrated that FBXO7 is deregulated in several cancers, such as lung cancer, colon cancer and endometrial cancer 19 , 24 . However, whether FBXO7 plays a role in HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%